ALQUR’AN DAN HADITH DALAM WACANA DELEGITIMASI NASIONALISME DI MEDIA ONLINE ISLAM - Miski Miski; Ali Hamdan (Al-A'raf : Jurnal Pemikiran Islam dan Filsafat, 2019)
This study tries to analyze the efforts of Islamic online media in constructing the discourse of delegitimation of nationalism, with the case study of eramuslim.com. With the constructivism paradigm, the ulumu Alqur'an, and critic of Sanad Hadith criticism, through the content analysis of articles in the media over a period of eight years, the results of the study show that the construction model of the discourse of delegitimation of nationalism used by eramuslim.com is a literal or denotative interpretation of the quranic verses and hadith which are considered to have a correlation with the problem of nationalism, as well as criticism of the nationalism system as a divisive people and ideology of fanaticism. There are also symptoms of strengthening the romanticism of religion in Islamic online media, along with symptoms of the obscurity of who has the right to talk about a particular issue.